Highly improved upconversion luminescence in NaGd(WO4)2:Yb3+/Tm3+ inverse opal photonic crystals. Issue 4 (10th December 2014) - Wang, Yunfeng; Xu, Wen; Cui, Shaobo; Xu, Sai; Yin, Ze; Song, Hongwei; Zhou, Pingwei; Liu, Xiaoyan; Xu, Lin; Cui, Haining
Abstract : The remarkable enhanced UCL properties in NaGd(WO4 )2 :Yb 3+ /Tm 3+ inverse opal photonic crystals. Abstract : The upconversion luminescence (UCL) of rare earth (RE) ions doped nanomaterials has attracted extensive interest because of its wide and great potential applications. However, the lower UCL efficiency is still an obstacle for real applications. Photonic modulation is a novel way to improve the efficiency of UCL. In this work, NaGd(WO4 )2 :Yb 3+ /Tm 3+ inverse opal photonic crystals (IOPCs) were fabricated through the polymethylmethacrylate (PMMA) template and the modification of the IOPC structure on the emission spectra and dynamics of Tm 3+ ions was systemically studied. It is interesting to observe that in the IOPCs, the high-order UCL 1 D2 – 3 H6 / 3 F4 was relatively enhanced. At the same time, the local thermal effect induced by laser irradiation was suppressed. Furthermore, the overall intensity ratio of visible UCL to near-infrared (NIR) down-conversion luminescence (DCL) was 2.8–8 times improved than that of the grinded reference (REF) and independent of the photonic stop band (PSB). The studies on UCL dynamics indicated that the nonradiative transition rate of Tm 3+ was considerably suppressed. The facts above indicated that in the IOPCs the UCL efficiency of Tm 3+ was largely improved due to the periodic macroporous structure.